2008
DOI: 10.1007/s11270-008-9644-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaccumulative Characteristics of Weed Species to Heavy Metals

Abstract: Phytoremediation, which mainly employs hyperaccumulators to remove heavy metals from contaminated soils, is receiving more attention world-wide. The identification of hyperaccumulators is still a key step for phytoremediation. This research is devoted to identify some plants with hyperaccumulative characteristics from weed species. In a pot culture experiment, the hyperaccumulative characteristics of 13 weed species in 11 families to Cd, Pb, Cu and Zn were examined. The result showed that Taraxacum mongolicum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, considering tolerance, accumulation, BCF, and TF properties together, only Carex tristachya indicated Cdhyperaccumulative characteristics. Wei et al also reported that some weed species displayed Cd-hyperaccumulative properties, such as Rorippa globosa, Conyza canadensis, Taraxacum mongolicum, and so on [15,18]. Considering the risk of heavy metals returning to the environment in the process of phytoextraction, plant shoots with accumulated heavy metals should be recovered and disposed of adequately.…”
Section: Accumulation and Translocation Of Metals In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considering tolerance, accumulation, BCF, and TF properties together, only Carex tristachya indicated Cdhyperaccumulative characteristics. Wei et al also reported that some weed species displayed Cd-hyperaccumulative properties, such as Rorippa globosa, Conyza canadensis, Taraxacum mongolicum, and so on [15,18]. Considering the risk of heavy metals returning to the environment in the process of phytoextraction, plant shoots with accumulated heavy metals should be recovered and disposed of adequately.…”
Section: Accumulation and Translocation Of Metals In Plantsmentioning
confidence: 99%
“…Ghosh and Singh [16] indicated that Ipomoea carnea was more effective in removing Cd from soil than the hyperaccumulator Brassica juncea. Solanum nigrum, Conyza canadensis, and Rorippa globosa were found to possess basic characteristics of a Cd-hyperaccumulator [17,18]. Muhammad et al [19] investigated wild plants growing around Pb-Zn sulfide terrain in the Kohistan region of northern Pakistan and found that Plectranthus rugosus, Rumex hastatus, Fimbristylis dichotoma, Heteropogon conturtus, and Myrsine africana were the best heavy metal accumulators.…”
mentioning
confidence: 99%
“…Since many plants have the tendency to assimilate metals from their surroundings, several species have been evaluated for their utility as biological monitors of environmental metal pollution [3][4][5][6]. A good biological monitor should be a species that is represented by large number of individuals over a wide geographic area and has a broad tolerance to metals and accumulates them at levels reflecting those present in the environment, so that its chemical composition will provide 2 Journal of Chemistry a measure of the magnitude of contamination when assessed against background values [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that some wild plants had the potential for phytoremediation of metal-contaminated soils (Wei et al 2008;Bareen and Tahira 2011). The advantages of applying weeds to phytoremediation are the large biomass' the adaptability of the environment, and the early growing season.…”
Section: Introductionmentioning
confidence: 99%